Transplantation of neurons derived from human iPS cells cultured on collagen matrix into guinea‐pig cochleae. (24th July 2015) - Ishikawa, Masaaki; Ohnishi, Hiroe; Skerleva, Desislava; Sakamoto, Tatsunori; Yamamoto, Norio; Hotta, Akitsu; Ito, Juichi; Nakagawa, Takayuki
Abstract: The present study examined the efficacy of a neural induction method for human induced pluripotent stem (iPS) cells to eliminate undifferentiated cells and to determine the feasibility of transplanting neurally induced cells into guinea‐pig cochleae for replacement of spiral ganglion neurons (SGNs). A stepwise method for differentiation of human iPS cells into neurons was used. First, a neural induction method was established on Matrigel‐coated plates; characteristics of cell populations at each differentiation step were assessed. Second, neural stem cells were differentiated into neurons on a three‐dimensional (3D) collagen matrix, using the same protocol of culture on Matrigel‐coated plates; neuron subtypes in differentiated cells on a 3D collagen matrix were examined. Then, human iPS cell‐derived neurons cultured on a 3D collagen matrix were transplanted into intact guinea‐pig cochleae, followed by histological analysis. In vitro analyses revealed successful induction of neural stem cells from human iPS cells, with no retention of undifferentiated cells expressing OCT3/4. After the neural differentiation of neural stem cells, approximately 70% of cells expressed a neuronal marker, 90% of which were positive for vesicular glutamate transporter 1 (VGLUT1). The expression pattern of neuron subtypes in differentiated cells on a 3D collagen matrix was identical to that of the differentiated cells on Matrigel‐coated plates. In addition, the survival of transplant‐derived neurons was achieved when inflammatory responses were appropriately controlled. Our preparation method for human iPS cell‐derived neurons efficiently eliminated undifferentiated cells and contributed to the settlement of transplant‐derived neurons expressing VGLUT1 in guinea‐pig cochleae. Copyright © 2015 John Wiley & Sons, Ltd.